2020
DOI: 10.13189/ujer.2020.080335
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Perceptions on the Impact of Flipped Learning on Student Learning and Teacher's Role in Jordanian Schools

Abstract: The current study investigated Jordanian teachers' perception on the impact of flipped learning on students' learning, teachers' role, and challenges facing its implementation. Teachers' perceptions were investigated in respect to their sex, experience, and teaching subjects. Participant in the study were all the (126) teachers who had already implemented flipped learning and they were considered innovative in their schools as they were the first to implement flipped learning in their teaching practices in Amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In the light of previous findings, the answer to the first question of the current study is achieved, as it has been confirmed that English teachers, at the intermediate school, apply the flipped classroom strategy to a large extent, consistent with the results of a study made by Alanzi (2020). These results also indicate positive attitudes among English teachers, at the intermediate school, towards the use of the flipped classroom strategy, which is consistent with the results of the Alsalami (2021), Alshehri (2021), Abuhumaid (2020) andKlabo (2018).…”
Section: Results Of the Studysupporting
confidence: 87%
“…In the light of previous findings, the answer to the first question of the current study is achieved, as it has been confirmed that English teachers, at the intermediate school, apply the flipped classroom strategy to a large extent, consistent with the results of a study made by Alanzi (2020). These results also indicate positive attitudes among English teachers, at the intermediate school, towards the use of the flipped classroom strategy, which is consistent with the results of the Alsalami (2021), Alshehri (2021), Abuhumaid (2020) andKlabo (2018).…”
Section: Results Of the Studysupporting
confidence: 87%
“…Covid-19 marked a before-and-after point in education where it was necessary to evaluate teachers and students' roles in the teaching-learning process [1]. A good teacher must locate, organize and adapt resources for various contexts [2], as technological advances have opened up significant teaching and learning opportunities [3]. For this reason, a growing number of teachers are integrating digital tools and social networks in their teaching [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Teachers main role is to ensure the integration of students in this process. In this aspect, teachers assume a crucial role in designing classroom environments that encourage students to become active and self-motivated learners (Abuhmaid, 2020). According to Bergman and Sams (2012), the FC approach is flexible as any teacher can personalize his/her work, while applying this method, taking into consideration courses and his/her students' needs.…”
Section: Teachers Roles Within a Flipped Classroommentioning
confidence: 99%